Perbedaan Daya Serap Hara Beberapa Varietas Unggul Padi pada Tipe Lahan Berbeda di Lahan Pasang Surut - Masganti, Masganti (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Nutrient uptake capacity is an important factor for increasing rice yield. A high nutrient uptake capacity is expected to produce a high rice yield. Research was conducted at Anjir Serapat Barat Village (Land type A), and Anjir Serapat Timur Village (Land type B) in the Kapuas Timur District, Central Kalimantan, during the planting season (PS) of 2006. The trial was arranged in a randomized complete block design with five treatments of three replications. The treatment consisted of 5 high-yielding rice varieties (IR66, IR64, Kapuas, Margasari, and Martapura) and each set was planted at two land types (Land types A and B). The variables observed were the N, P, K, Ca, and Mg uptakes by rice plants. Results showed that nutrient uptake capacities of rice plants were affected by rice varieties and by land types. The highest nutrient uptake capacity was found on variety Margasari grown on Land type A, which was equal to 55.2 kg K/ha, 47.6 kg N/ha, 19.7 kg P/ha, 19.7 kg Ca/ha, and 3.11 kg Mg/ha, followed by variety Martapura grown on Land type A, which was equal to 51.8 kg K/ha, 46.1 kg N/ha, 17.9 kg Ca/ha, 17.1 kg P/ha, and 9.7 kg Mg/ha. The lowest nutrient uptake capacity was found on variety Kapuas grown on Land type B, which was equal to 21.3 kg K/ha, 17.0 kg N/ha, 5.2 kg Ca/ha, 5.0 kg P/ha, and 2.8 kg Mg/ha. Differences on nutrient uptake capacity may influence the biomass and grain yield.